TWO YEARS FOLLOW UP AFTER ERADICATION THERAPY OF PEPTIC ULCER - RAJAB, HASSAN KHUDER; AL-SNAFI, ALI ESMAIL (International Journal of Current Pharmaceutical Research, 2020)
Objective: This study was performed to detect the recurrence rate for two years after eradication therapy of peptic ulcer. Methods: Sixty-nine patients included in this study in Kirkuk city from January 2004 to January 2005 as 1st year follow up, and 49 patients from January 2005 to January 2006 as second year follow up study. A urea breath test and re-endoscopic examination were carried out to confirm peptic ulcer recurrence. A questionnaire was prepared to take the history of the disease and other relevant data of each patient. Results: The recurrence was occurred in 6 (8.7%) and 8 patients (16.33%) in the 1st and 2nd years after eradication therapy. Highly risk of recurrence was smoking, age below 50 y and stress in 1st year follow up, and stress was the highly risk in the 2nd year follow up. Conclusion: After triple and quadruple therapy of peptic ulcer, the recurrence is low, However, the possibility of H. pylori resistance should be considered.